Splicing factors act as genetic modulators of TDP-43 production in a new autoregulatory TDP-43 Drosophila model. - Pons, M.; Miguel, L.; Miel, C.; Avequin, T.; Juge, F.; Frebourg, T.; Campion, D.; Lecourtois, M. (Human Molecular Genetics, 2017)
TDP-43 is a critical RNA-binding factor associated with RNA metabolism. In the physiological state, maintaining normal TDP-43 protein levels is critical for proper physiological functions of the cells. As such, TDP-43 expression is tightly regulated through an autoregulatory negative feedback loop. TDP-43 is a major disease-causing protein in Amyotrophic Lateral Sclerosis (ALS) and Frontotemporal Lobar Degeneration (FTLD). Several studies argue for a pathogenic role of elevated TDP-43 levels in these disorders. Modulating the cycle of TDP-43 production might therefore provide a new therapeutic strategy. In this study, we developed a new transgenic Drosophila model mimicking the TDP-43 autoregulatory feedback loop in order to identify genetic modulators of TDP-43 protein steady-state levels in vivo. First, we showed that our TDP-43_TDPBR Drosophila model recapitulates key features of the TDP-43 autoregulatory processes previously described in mammalian and cellular models, namely alternative splicing events, differential usage of polyadenylation sites, nuclear retention of the transcript and a decrease in steady-state mRNA levels. Using this new Drosophila model, we identified several splicing factors, including SF2, Rbp1 and Sf3b1, as genetic modulators of TDP-43 production. Interestingly, our data indicate that these three RNA-binding proteins regulate TDP-43 protein production, at least in part, by controlling mRNA steady-state levels.